Cementless Total Knee Arthroplasty Using a Highly Porous Tibial Baseplate in Morbidly Obese Patients: Minimum 5-Year Follow-Up - King, Bradley A.; Miller, Adam J.; Nadar, Arun C.; Smith, Langan S.; Yakkanti, Madhusudhan R.; Harwin, Steven F.; Malkani, Arthur L. (The Journal of Knee Surgery, 2022)
Morbidly obese patients undergoing cemented primary total knee arthroplasty (TKA) can pose a challenging problem with implant survivorship due to greater stress at the cement-bone interface. With the advent of additive manufacturing (three-dimensional printing), highly porous implants are now readily available. The purpose of this study was to review the results of primary TKA in the morbidly obese (body mass index [BMI] ≥ 40) patient using a highly porous cementless tibial baseplate. This is a retrospective study of 167 TKAs in patients with morbid obesity undergoing primary cementless TKA with a minimum 5-year follow-up. A total of 6 patients died and 14 were lost to follow-up, leaving 147 TKAs in 136 patients with a mean follow-up of 66 months (range 60–79 months). The average age was 59 years (range 36–84 years) and average BMI was 45 kg/m2 (range 39.5–63.9). Clinical results, patient-reported outcome measures, radiographs, and complications were reviewed. There were 9 failures requiring revision, including 3 for aseptic tibial loosening (2.0%), 2 for deep infection (1.4%), 2 for patellar resurfacing (1.4%), 1 for patella instability (0.7%), and 1 for extensor mechanism rupture (0.7%). Knee Society Score (KSS) improved from 48 to 90 at 2- and 5-year follow-up. KSS function score improved from 49 to 68 and 79 at 2- and 5-year follow-up, respectively. Survivorship with aseptic loosening as the endpoint was 98.0% at 5 years. Cementless TKA using a highly porous tibial baseplate in morbidly obese patients demonstrated excellent clinical results with 98% survivorship at 5 years and appears to offer durable long-term biologic fixation as an alternative to mechanical cement fixation in this challenging group of patients.
Keywords: primary TKA; cementless fixation; morbid obesity; aseptic loosening; survivorship